For this entire post, we have $r\ne1$, $n\in\mathbb N$. For the first half, $p\in\mathbb N$, and at the end $p\in\mathbb Q$.

It is well known that




But how do I evaluate


In closed form. I can see that

$$r\frac d{dr}\sum_{k=1}^nk^pr^k=\sum_{k=1}^nk^{p+1}r^k$$

$$\implies \sum_{k=1}^nk^pr^k=\underbrace{r\frac d{dr}r\frac d{dr}r\frac d{dr}\dots r\frac d{dr}}_p\frac{1-r^{n+1}}{1-r}$$

Though this is not really closed form. Any ideas on how to derive this general formula?

Secondly, how do I evaluate this for some $p\in\mathbb Q$? If I let $p=1/2$, for example, I get

$$\sum_{k=1}^n\sqrt kr^k$$

Though I have no idea how to evaluate it.

  • $\begingroup$ Thanks. CAS yields a 'closed form' in terms of $\texttt{PolyLogarithm}\ \mathrm{Li}$ and $\texttt{LerchPi}\ \Phi$. Namely, $\,\mathrm{Li}_{-p}\left(r\right) - r^{n + 1}\,\,\Phi\left(r,-p,n + 1\right)$ which is easily derived. $\endgroup$ – Felix Marin Nov 17 '16 at 18:05
  • $\begingroup$ @FelixMarin could you please post as an answer? $\endgroup$ – Simply Beautiful Art Nov 17 '16 at 20:21

AFAIK there is no closed form. One thing you can do: the sequence $$f(p) = \sum_{k=1}^n k^p r^k $$ has exponential generating function $$g(z) = \sum_{p=0}^\infty \dfrac{f(p) z^p}{p!} = \sum_{k=1}^n (r e^z)^k = \dfrac{(r e^z)^{n+1} - r e^z}{r e^z - 1}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.